대사증후군 환자의 삶의 질에 영향을 미치는 요인 - 한금선(Kuem Sun Han); 박영희(Young Hee Park); 김소남(So Nam Kim); 이숙자(Sook Ja Lee); 양승희(Seung Hee Yang) (Seuteureseu yeon-gu (Online), 2013)
본 연구는 대사증후군 환자의 지각된 스트레스, 우울, 건강생활양식, 삶의 질 정도를 파악하고, 이들의 상관관계를규명하여 대사증후군 환자의 삶의 질 향상을 위한 간호 중재 필요성에 대한 학문적 근거와 기초정보를 제공하고자시행하였다. 본 연구대상자는 서울 소재의 보건소 9곳에서 건강관리 중인 대사증후군 환자들을 편의 추출하였으며135명을 최종 연구대상자로 하였다. 대사증후군 환자의 삶의 질에 영향을 미치는 요인을 파악하기 위하여 지각된스트레스, 우울, 건강생활양식, 삶의 질을 조사였으며 수집된 자료는 빈도와 백분율, 평균과 표준편차를 구하고, 각변수 간에 상관관계분석 및 다중회기분석을 실시하였다. 연구 결과, 우울은 건강생활양식, 삶의 질과 유의한 수준의역상관관계를 나타났고 건강생활양식은 지각된 스트레스, 우울 변수 모두에서 역상관관계를 나타났다. 또한 대사증후군 환자의 삶의 질에 가장 강력한 삶의 질 영향요인은 우울이고 다음은 스트레스와 건강생활양식인 것으로 나타났다. 따라서 본 연구의 결과는 대사증후군 환자의 삶의 질 향상을 위해서 스트레스, 우울에 관한 간호 중재와 건강생활양식 실천을 높이는 간호중재 필요성의 중요함을 시사하는 바이며, 삶의 질 향상을 위해서 우울과 스트레스를관리하는 간호 중재 그리고 건강생활양식의 실천을 높이는 간호 중재 개발 연구를 활성화시키는 학문적 근거를 제시하는 바이다. The purpose of this study was to identify influencing factors on quality of life in patients with metabolic syndrome. Data were collected by self-reporting questionnaires on perceived stress, depression, lifestyle for health promotion and quality of life. The subjects of this study were 150 patients with metabolic syndrome. Data were collected from March 1 to April 30, 2013 at Nine public health centers in Seoul, Korea. Data were analyzed using Pearson correlation coefficients, and multiple regression by SAS 3.2 ver. The perceived stress, depression, lifestyle for health promotion were identified as factors influencing quality of life in patients with metabolic syndrome. The model explained 66% of the variables. Results suggest that health care giver should include strategies to decrease stress and depression and to increase lifestyle for health promotion in their intervention programs in order to improve the quality of life in patients with metabolic syndrome. (Korean J Str Res 2013;21:303∼311) KCI Citation Count: 9